Polymorphisms Related to Bovine Leptin Gene and Association with Productive and Reproductive Traits in Nellore Heifers - J. S. Fernandes; B. A. Crispim; L. O. Seno; R. R. Aspilcueta-Borquis; A. Barufatti (Faculty of Animal Science, Bogor Agricultural University, 2020)
The identification of genes and polymorphisms in female zebu related to the leptin gene that may be involved in better productive and reproductive performances is relevant to the livestock and economic sector. Thus, the objective of this study was to evaluate the SNP markers (T954M and C305T) and the BM1500 microsatellite and to analyze their associations with the traits of body weight, age at first calving (AFC), calving interval (CI), and reproductive efficiency (RE) in Nellore heifers. DNA extraction was performed, followed by the amplification of all markers. Association analyses were carried out with each marker and each traits separately. The result showed that no significant association was found between the reproductive traits and all markers and between body weight and both SNP markers. For the BM1500 microsatellite, the effect of the allele 138 (p=0.0383) on body weight was observed, with the growth curve for this allele being related to the lower asymptotic weight. Therefore, the BM1500 microsatellite marker was the only one with a significant association with a productive trait providing information about the condition of body weight in Nellore heifers.